The Efficiency of Ascaris Spp. Eggs Inactivation in Sewage Sludge by Lime Dosage, Ammonia Concentration, and Temperature Variation - Barti Setiani Muntalif; Mayrina Firdayati; Husna Muizzati Shabrina (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Ascaris spp. eggs threaten sludge reuse because they are usually more environmentally resistant than other microorganisms. Consequently, the WHO recommended an acceptable limit of <1 helminth egg per gram of total solid as a health-based target for treated feces and fecal sludge and aimed to ascertain the effectiveness and reduction rate of Ascaris spp. eggs in sludge at various lime doses, ammonia concentrations, and temperature values. Methods: Eggs were detected and enumerated using the flotation and sedimentation principle. The reduction process was performed in batches with quick lime doses of 30% and 50% w/w, ammonia concentrations of 1,000 and 5,000 mg/L, and temperatures of 30°C and 50°C. Results and Discussion: The number of eggs of Ascaris spp. fertile in the ponds was 1.38 ± 1.38 eggs/gram to 42.98 ± 13.09 eggs/gram, and the infertile amount was 0.46 ± 0.80 eggs/gram to 17.82 ± 6.55 eggs/gram. Using a temperature of 40°C, 50% CaO, and 5,000 ppm ammonia resulted in the highest percentage of reduction, 97.98 - 98.09% but 1.12 eggs/gram was remaining. Conclusion: Higher pH and ammonia levels primarily affect egg decrease in Ascaris spp. To reduce 99% of Ascaris spp. eggs until it reaches <1 egg/g, a dose of 50% CaO is required, with 5,000 ppm ammonia at a temperature of 40°C for 2.7 hours.